Comparing the efficacy of low dose and conventional dose of oral isotretinoin in treatment of moderate and severe acne vulgaris - Gita Faghihi; Fatemeh Mokhtari; Nasrin Motamedi Fard; Narges Motamedi; Sayed Mohsen Hosseini (Wolters Kluwer Medknow Publications, 2017)
Objective: This study was conducted to compare the effect of low-dose isotretinoin with its conventional dose in patients with moderate and severe acne. Methods: This was a clinical trial conducted on 60 male and female patients with moderate and severe acne vulgaris. The patients were divided into two treatment groups: 0.5 mg/kg/day isotretinoin capsule and low-dose isotretinoin capsule (0.25 mg/kg/day). Patients in both groups received 6-month treatment. At the end of the 6th month and 12th month (6 months after the end of the treatment), they were examined again, and their improvement was determined and compared. Findings: The average severity of acne in the two treatment groups did not differ significantly within any of the study periods. The most common side effects were nose dryness in the low-dose group (17%) and hair thinning and loss in the conventional - dose group (33.2%), although all the patients had dry lips. Conclusion: According to the same severity of the acne in two groups in different study periods, as well as fewer side effects and more patients' satisfaction, the low-dose isotretinoin can be considered in the treatment of acne.